Solvation-Driven Electrochemical Actuation - Boldini, Alain; Cha, Youngsu; Porfiri, Maurizio (AMER PHYSICAL SOC, 2021)
We demonstrate a novel principle of contactless actuation for ionic membranes in salt solution based on solvation. Actuation is driven by differential swelling of the sides of the membrane, due to comigrating water in the solvation shells of mobile ions. We validate our theory through a series of experiments, which unravel a strong dependence of membrane deflection on the hydration numbers of mobile ions in the external solution and membrane. Our study suggests a critical role of solvation in the chemoelectro-mechanics of natural and artificial selectively permeable membranes.
Keywords: ION SOLVATION; WATER; NAFION; DYNAMICS; TRANSPORT; MEMBRANES; HYDRATION; ANGLE; GELS